Universo primitivo com poeira e gás de Chaplygin - Mattos Novaes da Rocha, Nathália; Amaral Monerat, Germano; Gimenes Alvarenga, Flávio; Vitorino de Borba Gonçalves, Sergio; Oliveira-Neto, Gil; Vasquez Corrêa Silva, Eduardo; Guerra Marques dos Santos Mello, Cássia (Cadernos de Astronomia, 2024)
Summary of the poster presented in the second edition of the As Astrocientistas event, held between 7 and 10 February2023.
Keywords: Cosmology; Primordial Universe; Chaplygin gas